Datos para la historia de la prensa deportiva en Cataluña. - Berasategui, María Luisa (Revista General de Información y Documentación, 2000)
The article offers a historical overview of the major mastheads in the Catalonian press from the second half of the nineteenth century to the Spanish Civil War, with a special mention to sports humor. It proposes the use of a spe cific record for this kind of press, also considering te maintenance of its col lection of ancient items.